A new synonym of Ptilagrostis yadongensis and a new record of Stipa bhutanica to the flora of China (Poaceae) - Zhang, Zhong-Shuai; Zhu, Xiang-Yun; Li, Ling-Lu; Jiang, Shan-Wen; Chen, Wen-Li (Phytotaxa, 2016)
Ptilagrostis Grisebach (1852: 447) is a small genus of the grass family, including approximately 11 species (Wu & Phillips 2006, Barkworth 2007). It occurs in both Asia and North America with about eight species distributed in Qinghai-Tibet Plateau, its diversity center. Ptilagrostis yadongensis Keng & Tang (1985: 44) is one of the species that occurs in this region, which was described based on materials from Yadong, China, the southern slope of Himalayas. The paper was published in a Chinese journal, viz. Journal of Southwest Agriculural University, and had not been noticed until 2005 (Peterson et al. 2005, Wu & Phillips 2006). The author pointed out that P. yadongensis is distinguished from its morphological close, Ptilagrostis concinna (Hooker 1897: 230) Roshevitz (1934: 75) by linear panicles with fewer spikelets, longer and unequal glumes, and shorter and glabrous anthers.